A risk-scoring system to predict dupilumab-associated ocular surface disease in patients with atopic dermatitis - Shim, Sunyoung; Kim, Jung Sun; Yee, Jeong; Gwak, Hye Sun (Frontiers in Pharmacology, 2024)
Introduction: Dupilumab is the first biological treatment for atopic dermatitis (AD).Dupilumab-associated ocular surface disease (DAOSD) is one of the most commonly reported side effects in patients with AD during dupilumab treatment. This study aimed to identify risk factors for DAOSD in a real-world setting and construct a risk-scoring system for predicting DAOSD risk.Methods: A retrospective analysis was conducted for dupilumab-treated adult patients with AD between April 2019 and September 2023 at Yeouido St. Mary's Hospital in Korea. Patients aged ≥ 18 years who received dupilumab to treat AD were included. Univariate and multivariable logistic regression analyses were performed to determine independent risk factors for DAOSD. A risk scoring system was constructed to predict DAOSD risk based on the adjusted odd ratios of significant variables.Of the 97 dupilumab-treated patients, 28 (28.9%) developed DAOSD. Among them, three (10.7%) patients discontinued dupilumab due to ocular side effects. In the multivariable analysis, older age, history of conjunctivitis, and a baseline Eczema Area and Severity Index (EASI) score ≥ 28 were independent risk factors for developing DAOSD. Using these variables, a risk-scoring system was constructed. The predicted DAOSD risks for AD patients with 0, 1, 2, 3, 4, and 5 points were 5.8%, 14.2%, 30.7%, 54.3%, 76.2%, and 89.6%, respectively.In this study, the patient's age, history of conjunctivitis, and higher baseline EASI score were significantly associated with DAOSD. This risk-scoring system would help identify high-risk patients requiring more caution when initiating dupilumab treatment.